The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/sms.13561
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and all‐cause mortality: A 15‐year follow‐up using a compositional data analysis

Abstract: The association between the composition of movement behaviors and mortality risk, acknowledging the composition nature of daily time data, is limited explored. The aim was to investigate how the composition of time spent in sedentary behaviors (SB), light intensity physical activity (LIPA), and moderate‐to‐vigorous physical activity (MVPA) is associated with all‐cause mortality, in a cohort with 15 years follow‐up time, using compositional data analysis. Eight hundred fifty‐one participants (56% women, mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
(99 reference statements)
5
28
1
2
Order By: Relevance
“…This study adds to the existing literature by showing that multiple activity variables differ between physical activity profiles associating with different mortality risks. It also demonstrates considerably larger effect sizes than in previous reports on the same population 6,14 . Even if this study cannot for sure identify which physical characteristics are most important for decreasing all‐cause mortality, the correlation between the characteristics suggest a complex interplay.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This study adds to the existing literature by showing that multiple activity variables differ between physical activity profiles associating with different mortality risks. It also demonstrates considerably larger effect sizes than in previous reports on the same population 6,14 . Even if this study cannot for sure identify which physical characteristics are most important for decreasing all‐cause mortality, the correlation between the characteristics suggest a complex interplay.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous findings from the same cohort as in this study have shown an inverse relationship between MVPA and mortality, and replacing SB with time spent in LIPA and MVPA has been found to have beneficial effect for all-cause mortality. 6,12 This study adds to the existing literature by showing that multiple activity variables differ between physical activity profiles associating with different mortality risks. It also demonstrates considerably larger effect sizes than in previous reports on the same population.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…As more minutes are added to LIPA, it is estimated that the associated HR will increase if this time is taken from MVPA, but decrease if this time is taken from sleep or SED. Substitutions were not made beyond the range of the 2.5th to 97.5th percentile of minutes per day spent in each movement behaviour (e.g., no more than 75.4 min per day were added to the mean 16.8 min per day spent in MVPA) composition and all-cause mortality but did not include sleep data [41]. Lacking information on sleep limited the ability of these authors to consider all co-dependent parts of the 24-h movement behaviour composition within a CoDA paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve informatization and standardization of physical education management in colleges and universities, it must develop a physical education management system. Through the development of the student physical education management system, the physical education management system of colleges and universities realizes management Informa ionization and standardization [11,12]. By improving the efficiency of sports information management, this will not only greatly improve the efficiency of student sports management information in colleges and universities but also further improve the physical fitness of students [13,14].…”
Section: Introductionmentioning
confidence: 99%